Volumetric error modeling and prediction for machine tools based on key component tolerance - Jinwei Fan; Zhuang Li; Ri Pan; Kun Sun; Kai Chen (Alexandria Engineering Journal)
Accurate volumetric error model is the basis for accuracy design. In this paper, a universal model for volumetric error prediction considering tolerance is proposed. Firstly, geometric error parameters are obtained by analysing the motion forms of key components. Secondly, the map between geometric error and tolerance is developed using Fourier function. Subsequently, the volumetric error prediction model (VEPM) is established based on key component tolerance. The model was applied to guide the development of machine tools. Finally, model validation experiments are carried out with two configurations of machine tools. The results show that, for the horizontal grinder, the predicted values for ±45° diagonal errors are 0–2.7 μm and 0–4.5 μm, which are consistent with the measured average values of 0.03–2.33 μm and −0.10–5.46 μm, respectively. Moreover, the predicted and measured values for +45° diagonal error of the vertical grinder are −15.0–0 μm and −15.07–0 μm, respectively. The experimental results illustrate the VEPM is effective and universal. The model has the potential to be applied to the design and development of machine tools.